Broadcast cancellation in search mechanisms - Lima, R. (2013)
Searching for resources over unstructured networks is usually supported by broadcast communication primitives. Ideally, the broadcast process should be cancelled as soon as possible after a successful discovery, to avoid ooding the entire network. However, cancelling an ongoing broadcast is challenging and may increase the number of exchanged messages. In this paper, we compare the cancellation mechanisms used by BERS and BERS? With new proposed cancellation approaches BCIR and BCIR? The formulation of a simplified analytical model and the simulation results show that:i)it is possible to reduce the number of retransmitted messages, without increasing the latency observed in BERS?; and ii) BCIR is more energy eficient, which can contribute to extend the availability of mobile battery powered devices.